The Europeanisation of social protection - Saari, Juho; Kvist, Jon (Book collections on Project MUSE., 2007)
This collection focuses on the relationship between social care, community and citizenship, linking them in a way relevant to both policy and practice. While there is extensive research within each of these fields, until now there is a dearth of dialogue between them. In the current political context. With an emphasis on the development of locally based services and governance, this publication is particularly timely. Divided into four sections, it covers: key concepts, issues and relationships and draws on contrasting illustrations from England and Scotland; ethics of care and the theoretical and moral complexities to be thought through for both those receiving and those delivering care; practice based chapters on community capacity to care, black and minority ethnic care, anti-social behaviour, domestic violence, befriending, volunteering, dementia care and home care; and international comparisons and perspectives with chapters from Sweden, Germany and Japan. The book is aimed at a wide range of readers including: academics, principally teachers and researchers in social policy and social work; undergraduate and postgraduate students; practitioners, including community development workers, social workers, public health workers, mental health staff, practitioners employed on renewal, regeneration, social inclusion and community cohesion programmes and policy makers in central and local government, strategic health authorities and primary care trusts. It opens up discussions relevant for the next decade and beyond.